Men’s knowledge on body care: a cartographic study - Cleiry Simone Moreira da Silva; Álvaro Pereira; Paulo Sérgio da Silva; Nébia Maria Almeida de Figueiredo (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to identify men’s knowledge on body care. Method: it is a cartographic study with a qualitative approach. The research was conducted with 70 men in the city of Boa Vista, state of Roraima. The strategy for data production was called the meeting. Participants were encouraged to think about epistemic units, care and body, from models that were recorded and their meanings transcribed for content analysis according to Bardin. Results: 282 units of decoded records such as body hygiene, sexual health and physical exercise were evidenced. In the decoding units, the conscious, functional male body is discussed, which serves for health professionals to think about caring approaches. Final considerations: cartographic forays allowed the male body to be recognized for its functionality, with structured knowledge on care in three dimensions: body hygiene, sexuality and sports practices.